106 Progesterone Release in Controlled Internal Drug Release Devices Using Different Sterilization Methods. (1st March 2018) - Vincent, K; Roper, D; Snyder, D; Jones, T; Talsma, B
Abstract: The use of Controlled Internal Drug Release devices (CIDRs) have been used widely in the livestock industry to aid in estrus synchronization. It has become common practice to re-use CIDRs to reduce management costs. Effectiveness of twice used inserts has recently been investigated, however practical means of disinfection are warranted. Objectives of the current study were to evaluate efficiency of re-used CIDRs, identify potential disinfectant methods to minimize cost, as well as to test if prolonged storage of CIDR affects progesterone release. Two experiments took place; Replication 1 (Fall 2016) and Replication 2 (Spring 2017); with sample sizes of twenty-nine and thirty-six angus-cross bred cows, respectively. Animals were blocked by age (avg. 4 yr) and randomly assigned into a treatment group. Each animal received a CIDR disinfected in one of four treatment which included; new (CONT), autoclaved (AUTO), dishwasher (DISH) and chlorhexidine disinfected (CHLO). AUTO treatment CIDRS were processed and autoclaved at 121º C and 724 mmHg for 20 mins, DISH disinfected CIDRs were placed in a dishwasher and processed through one hot cycle (70 º C) on high with chlorhexidine as the detergent, and in CHLO treatment the inserts were soaked in approximately 15 L of hot water (50º C) which included approximately 200 ml of chlorhexidine solution. The experimental period lasted 7 days with blood samples collected via coccygeal tail vessel at 0, 72, 168 ± 2 h relative to CIDR insertion time. Animals were the experimental unit, and dependent variables were analyzed using PROC MIXED with repeated measures. Interactions were not observed between Replication 1 and Replication 2 for treatments, however, a replication effect was observed ( P =0.0012). Higher overall progesterone levels were reported in fall 2016 compared to spring 2017. Overall plasma progesterone concentrations were not affected ( P= 0.24) by CIDR treatment (AUTO, 3.31 ± 0.62 ng/ml; CHLO, 3.86 ± 0.62 ng/ml; DISH, 4.18 ± 0.60 ng/ml) when compared to the control (CONT, 2.75 ± 0.60 ng/ml). Disinfecting single-use CIDRs with chlorhexidine and warm water solution allows for a second use without affecting progesterone release. These results support previous research findings of the effectiveness of single-use CIDRs in elevating progesterone in the blood. Progesterone levels in cows receiving the CHLO CIDRs did not differ from cows with new CIDRs, indicating that this method for disinfecting CIDRs for reuse is effective and may present a method to lower cost associated with estrus synchronization.